Neural Mechanisms Underlying Individual Differences in Control-Averse Behavior - Rudorf, Sarah (J Neurosci, 2018)
When another person tries to control one's decisions, some people might comply, but many will feel the urge to act against that control. This control aversion can lead to suboptimal decisions and it affects social interactions in many societal domains. To date, however, it has been unclear what drives individual differences in control-averse behavior. Here, we address this issue by measuring brain activity with fMRI while healthy female and male human participants made choices that were either free or controlled by another person, with real consequences to both interaction partners. In addition, we assessed the participants' affects, social cognitions, and motivations via self-reports. Our results indicate that the social cognitions perceived distrust and lack of understanding for the other person play a key role in explaining control aversion at the behavioral level. At the neural level, we find that control-averse behavior can be explained by functional connectivity between the inferior parietal lobule and the dorsolateral prefrontal cortex, brain regions commonly associated with attention reorientation and cognitive control. Further analyses reveal that the individual strength of functional connectivity complements and partially mediates the self-reported social cognitions in explaining individual differences in control-averse behavior. These findings therefore provide valuable contributions to a more comprehensive model of control aversion. SIGNIFICANCE STATEMENT Control aversion is a prevalent phenomenon in our society. When someone tries to control their decisions, many people tend to act against the control. This can lead to suboptimal decisions such as noncompliance to medical treatments or disobeying the law. The degree to which individuals engage in control-averse behavior, however, varies significantly. Understanding the proximal mechanisms that underlie individual differences in control-averse behavior has potential policy implications, for example, when designing policies aimed at increasing compliance with vaccination recommendations, and is therefore a highly relevant research goal. Here, we identify a neural mechanism between parietal and prefrontal brain regions that can explain individual differences in control-averse behavior. This mechanism provides novel insights into control aversion beyond what is accessible through self-reports.